Islamic finance why it makes sense (for you) - Vicary Abdullah, Daud, 1951-; Chee, Keon (Marshall Cavendish Business, 2014)
An essential guide to understanding Islamic finance, its principles and how it works. Fully updated and revised.New topics - microfinance,the ethical company and wealth succession. Comprehensive information presented in clear, concise writing.Easy-to-understand examples, charts and diagrams. Authors are experts in finance matters.